FACTORS AFFECTING THE PERFORMANCE OF DRIVER : THE EXPERIENCE OF TRANSJAKARTA BUS DRIVER - Hendy Tannady, Ismuhadjar & Alex Zami (International Journal of Research Science and Management, 2017)
A bus driver’s performance is important in ensuring the smoothness and safety of a journey. By the end of year 2016 123,7 million people in province of Jakarta used the service of transjakarta. The study was conducted in 5 routes of Transjakarta. From a preliminary survey of 100 passenger using 15 questions to measure passengers' perceptions of the performance of transjakarta bus driver, it was concluded that 58% of respondents rated the performance of transjakarta bus driver in the province of Jakarta is still poor and needs to be improved.The purpose of this study is to examine the factors that affect performance of transjakarta bus driver, based on a series of theories and descriptions of what factors affect performance, compensation and self-efficacy were selected as two exogenous variables